I Came Into This With Nothing To Write About - Jardine, David; Baeza Hidalgo, Catalina; Puley, Ken; Smith, David (Philosophical Inquiry in Education, 2026)
This is a collection of various solo and co-written bits and pieces all variously focusing old age and its lived-experiences, the arts of writing, the idea of "the whole" in the language of some writing on ecologically alert education, early childhood education, attention to particulars, encouraging students new to the fields of education and the teaching and learning that ensues, an old book read over 50 years ago (!) and ecological pedagogy.